2013
DOI: 10.1111/pme.12106
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Anterior Ultrasound-Guided Superior Hypogastric Plexus Neurolysis in Pelvic Cancer Pain in Advanced Gynecological Cancer Patients

Abstract: The anterior USG-guided superior hypogastric plexus neurolysis is a useful technique in relieving pelvic pain in gynecological malignancies. However, it requires expertise to perform the block. It also avoids the radiation exposure involved with computed tomography-guided and fluoroscopy-guided superior hypogastric block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…SHPB produced a significant decrease in pain intensity and a less morphine consumption in comparison with pharmacological approach, while no statistical differences in adverse effects were found (Mishra et al, 2013). Pelvic pain is even more complex than pancreatic pain, for which CPB is performed, and often multiple pain mechanisms are involved.Somatic pain and neuropathic pain often coexist and mixed syndromes are more likely to be observed in patients with pelvic tumors than in those with abdominal pain caused by pancreatic cancer (Mercadante et al, 2002).…”
Section: B) Shpbmentioning
confidence: 83%
See 1 more Smart Citation
“…SHPB produced a significant decrease in pain intensity and a less morphine consumption in comparison with pharmacological approach, while no statistical differences in adverse effects were found (Mishra et al, 2013). Pelvic pain is even more complex than pancreatic pain, for which CPB is performed, and often multiple pain mechanisms are involved.Somatic pain and neuropathic pain often coexist and mixed syndromes are more likely to be observed in patients with pelvic tumors than in those with abdominal pain caused by pancreatic cancer (Mercadante et al, 2002).…”
Section: B) Shpbmentioning
confidence: 83%
“…Mishra et al, (Mishra et al, 2013) randomized fifty patients with pelvic cancer pain associated with gynaecological cancer to receive either ultrasound-guided SHPB and oral morphine or oral morphine only. Patients treated with the block had a decrease in pain intensity and a less morphine consumption, while no statistical differences in adverse effects were found.…”
Section: B) Shpbmentioning
confidence: 99%
“…Other disadvantages include radiation hazards, discitis in a transdiscal approach, and inability to identify vascular and other peritoneal structures. Recently an ultrasound-guided technique for SHPB has been described for patients with cancer (10). The procedure was verified in a cadaveric study and confirmed using fluoroscopy (11).…”
Section: Discussionmentioning
confidence: 87%
“…It is known that SHPB prevents transmission of pelvic pain signals to the central nervous system. Previous studies showed reduced pain and morphine consumption with SHPB compared to placebo or sham treatment in women with gynecologic cancer [4] and in those who underwent hysterectomy [5] or UAE [6]. Furthermore, a single-center, retrospective evaluation of UAE patients revealed lower peroral morphine-equivalent consumption with SHPB compared to EDA [7].…”
Section: Introductionmentioning
confidence: 89%